Using a Network of Low-cost Particle Sensors to Assess the Impact of Ship Emissions on a Residential Community - Rohan Jayaratne; Tara Kuhn; Bryce Christensen; Xiaoting Liu; Isak Zing; Riki Lamont; Matthew Dunbabin; Jill Maddox; Gavin Fisher; Lidia Morawska (Aerosol and Air Quality Research)
Abstract Shipping emissions are known to affect communities in coastal locations, especially near harbours. This study monitored the air quality near the premier cruise ship terminal in Melbourne over a continuous period of 98 days during the peak cruise ship season in Australia. As shipping emission plumes are intermittent and fluctuate spatially, they cannot be detected accurately by a single fixed monitor. To overcome this limitation, we deployed seven units of the low-cost KOALA air quality monitor, which measures PM2.5 and CO concentrations in real time and then transmits the data via 3G to an in-cloud database, in a spatially distributed configuration, four at ground level and three on the upper balconies of two high-rise apartment blocks. The time profile showed numerous spikes in the PM2.5 concentration, some of which exceeded 200 µg m−3 for periods of 5–10 min, coinciding with ship movements. On average, the spikes were ~4–5 times above the normal background value (~10 µg m−3). Because of their very short duration, these episodes did not significantly raise the 24-h averages at any of the locations; however, they increased the number of days on which these values exceeded the limit specified by the national air quality standard, resulting in more exceedance days for the monitored area than the nearest air quality station. Although the long-term health effects of elevated PM concentrations are known, few studies have been conducted on the risks of short-term exposures to extreme spikes.